Prediction and early prevention of violence in children and adolescents - Ф. Сафуанов; А. Құдайбергенова; Э. Калымбетова; А. Урисбаева; А. Сулейменова (Хабаршы. Психология және социология сериясы)
This study addresses the issue of violence among children and adolescents. Its primary goal is to determine the prevalence of violence in families and educational institutions and to identify the key psychological and social contributing factors. A questionnaire developed by educational psychologist T. V. Loginova was used. An anonymous survey involved 94 adolescents aged 13 to 17. Data were processed using IBM SPSS Statistics 26 with Fisher’s exact test, Pearson’s chi-squared test, Phi coefficient, and Cramer’s V. Results revealed a statistically significant correlation between family relationships and adolescents’ tendency toward violence. Additional factors considered included education level, social status, and emotional condition. The research integrates quantitative and qualitative methods. Theoretical significance lies in explaining the influence of family and school on adolescent behavior. The results are very useful because they may be used in schools, social assistance centers, and programs that teach parents how to keep their kids from becoming violent.  This research adds important information to the area and encourages the creation of more programs.